The social capital as an instrument for the economic analysis - Sánchez Jiménez, Vicente (Cuadernos de Relaciones Laborales, 2013)
The relations between the economy and the culture is tried to be analyzed in this paper under the theorizing of the social capital, underlying the relevance of the cultural factors as the structural principle of the society and as another piece of the wealth of nations. The confidence stands out among these factors as the base of the modern economic process. An attempt of proving the influence that the social vision is having on the economic research over the last decades is carried out. This aim is tried by means of the establishment of this reality and its inclusion in the analysis of the economic development and the poverty eradication.
Keywords: social capital; economic development; social structural element